OF THE EFFICIENCY OF THE USE OF RECONSTRUCTIVE PLATES AND SCREWS IN SHELTERED FRACTURE OF THE DISTAL END OF THE HUMERUS - Mirzaev Ravshanbek Khoshimovich; Shopulatov Iskandar Bakhtiyorovich; Khoshimov Djavokhir Ravshanbekovich (Scholar Express Journal, 2022)
The article presents surgical methods for the treatment of patients with comminuted fractures of the distal end of the humerus in 79 patients. The patients were divided into three groups depending on the method of surgical treatment. The results of treatment of surgical methods of all three groups were studied and conclusions were drawn. The proposed method of the authors proved the effectiveness of the treatment of fractures of the humerus.
Keywords: Bones; plates; humerus; treatment; injury